Equivalent norms of Herz-type Besov and Triebel-Lizorkin spaces - Jingshi Xu (Journal of Function Spaces and Applications)
In this paper the author obtains equivalent norms of Herz-type Besov and Triebel-Lizorkin spaces, which are generalizations of well-known Herz-type spaces and inhomogeneous Besov and Triebel-Lizorkin spaces.